Selective Determination of Copper in Water Samples by Atomic Absorption Spectrometry after Cloud Point Extraction - KÖK YETİMOĞLU, ECE; AYDIN URUCU, OYA (TAYLOR & FRANCIS INC, 2010)
A preconcentration methodology utilizing the cloud point phenomenon is described for the determination of copper by flame atomic absorption spectrometry. The reagent Sulfathiazolylazo resorsin was used as a complexing agent. The preconcentration factor of 25-fold was obtained. The calibration curve is linear in the range of 4-400 mu gL-1 with a limit of detection of 0.64 mu gL-1. The relative standard deviation (n=5, 12 mu gL-1) was 3.5%. The cloud point is formed in the presence of phenol at room temperature. The method was successfully applied to the determination of copper in water samples and a standard reference material.
Keywords: Atomic absorption spectroscopy; Cloud point extraction; Copper; Preconcentration; Sulfathiazolylazo resorsin; ORGANIC ADDITIVES; PRECONCENTRATION; CU